Translational Personas and Hospital Library Services. Issue 3 (2nd July 2020) - Gonzales, Sara; O'Keefe, Lisa; Gutzman, Karen; Viger, Guillaume; Wescott, Annie B.; Farrow, Bailey; Heath, Allison P.; Kim, Meen Chul; Taylor, Deanne; Champieux, Robin; Yen, Po-Yin; L. Holmes, Kristi
ABSTRACT: Academic health centers, CTSA hubs, and hospital libraries experience similar funding challenges and charges to do more with less . In recent years academic health center and hospital librarians have risen to these challenges by examining their service models, and beyond that, examining their patron base and users' needs. To meet the needs of employees, patients, and those who assist patients, hospital librarians can employ the CTS Personas, a project of the Clinical and Translational Science Awards (CTSA) Program National Center for Data to Health. The Persona profiles, which outline the motivations, goals, pain points, wants, and needs of twelve employees and two patients in translational science, provide vital information and insights that can inform everything from designing software tools and educational services, to advertising these services, to designing impactful and collaborative library spaces.